THE EFFORTS ON SUSTAINABILITY OF THE ACHIEVEMENT FKMP ON QS WORLD UNIVERSITY RANKING TOP 300 BY SUBJECT - Nasir, N. F.; Yusof, Y. (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2015)
This article review each vital elements and aspects that contribute to sustain recent achievement of Faculty of Mechanical and Manufacturing Engineering (FKMP), Universiti Tun Hussein Onn Malaysia by the QS world university ranking by subject in 2015. Some of recent and important issues are discussed and reviewed. The suggestions for improvements are also raised out for further reference.